Services for Women Leaving Prison in Canada: Results of a Brief Environmental Scan - Heggie, Clare; Bray, Mirinda; Paynter, Martha (Canadian Journal of Nonprofit and Social Economy Research / Revue canadienne de recherche sur les OSBL et l’économie sociale, 2025)
Women are a growing population in prisons in Canada. When women leave prison, community-based organizations (CBOs) can provide immediate material resources, and facilitate connection to healthcare and other services. We conducted an environmental scan of CBOs that support women leaving prison in order to identify potential gaps in service delivery, and identified 86 CBOs distributed across ten provinces, with a lack of services in rural areas and a general lack of housing. The rapid growth in the incarceration of women has not been met with an investment in CBOs. We call for an investment in, and increased attention towards, community-based housing as both a reentry service and an alternative to incarceration.